Pulse of the People : Political Rap Music and Black Politics - Bonnette-Bailey, Lakeyta M. (Lakeyta Monique), 1981- (Book collections on Project MUSE., 2015)
Examining the history of rap music, particularly the subgenre of political rap, and coupling public opinion research with lyrical analysis, Lakeyta M. Bonnette illustrates the ways rap music serves as a vehicle for the expression and advancement of political thought in urban Black communities.